New Advancements in Herbicide Spraying - Ramdas Kanissery; Mahesh Bashyal; Ioannis Ampatzidis; Stephanie S. Teems (EDIS, 2022)
Chemical weed control using herbicides is essential for profitable citrus production as it reduces the competition from weeds. This article explores the use of herbicide spraying technologies, such as using sensors and artificial intelligence to increase herbicide use efficiency and eliminate negative environmental impacts.